PENGARUH VOUCHER DISKON GOFOOD DAN GAYA HIDUP HEDONISME TERHADAP PEMBELIAN IMPULSIF PADA MAHASISWA DI APLIKASI GOJEK - Ariyani, Rina; Lestari , Flony Syera; Putra, Hery Tiyas Pramana; Zikrinawati, Khariani; Fahmy, Zulfa (Investama : Jurnal Ekonomi dan Bisnis, 2023)
One of the service-based applications that provide food purchase is a Gojek through a Gofood feature. A discount voucher on the application can have an effect on the user as well as on college students. The purpose of the study is to test the impact of Gofood discount vouchers on Gojek and hedonism on impulse purchase among students on food product purchases. The method used in this study is the quantitative study method. The data analysis used to test hypotheses on this study using Multiple linear Regression analysis, which is it used to determine the influence of independent variables on the dependent variable. Based on the conducted test, it is shown that there is an influence between variables X and X1 on variable Y with a significance result of 0.000 < 0.05, which means that discount vouchers and hedonistic lifestyle have an influence on impulsive purchasing among students in food product purchases on the Gojek application.